Mechanical, chemical, structural analysis and comparative release of PDGF-AA from L-PRF, A-PRF and T-PRF - an in vitro study - Shravanthy Ravi; Muthukumar Santhanakrishnan (Biomaterials Research, 2020)
Abstract Background Platelet concentrates have been popularly used in regenerative periodontal therapy as they are autologous in origin and they provide a supernatural concentration of platelets, growth factors and leukocytes. The release profile of various growth factors is considered important during the various phases of wound healing with the most important being the inflammatory phase where the release of the growth factors help in recruitment of cells and in collagen production. With the more recent modifications of PRF namely A-PRF and T-PRF, the mechanical and chemical degradation properties have also improved. The aim of the present study was to correlate the release profile of PDGF-AA from various forms of platelet concentrates (L-PRF, A-PRF, T-PRF) based on their mechanical and chemical properties. Methods Blood samples were drawn from 2 male and 3 female systemically healthy patients between 20 and 25 years of age who were about to undergo periodontal regeneration for PRF preparation. The blood sample was immediately centrifuged using a table top centrifuge (Remi R4C) at 1060 rpm (208 x g) for 14 min for A-PRF preparation, 1960 rpm (708 x g) for 12 min for L-PRF preparation and 1960 rpm (708 x g) for 12 min in titanium tubes for T-PRF preparation. Tensile test was performed using universal testing machine. The in vitro degradation test of the prepared PRF membranes were conducted by placing the PRF membrane in 10 ml of pH 7.4 PBS on an orbital shaker set at 50 rpm. SEM evaluation of the PRF membrane was done under both low and high magnification. In order to determine the amount of released growth factor PDGF-AA at 15 min, 60 min, 8 h, 1 day, 3 days, and 10 days, samples were placed into a shaking incubator at 37 °C to allow for growth factor release into the culture media. Results On comparing the three PRF membranes, it was found that T-PRF contained the maximum tensile strength (404.61 ± 5.92 MPa) and modulus of elasticity (151.9 ± 6.92 MPa). Statistically significant differences between the three groups were found on comparing the groups for their mechanical properties. In the degradation test, it was found that the maximum amount of degradation was found in L-PRF (85.75%), followed by A-PRF (84.18%) and the least was found in T-PRF (82.27%). T-PRF released the highest amount of PDGF-AA (6060.4 pg/ml) at early time points when compared to A-PRF (5935.3 pg/ml). While T-PRF had rapid release of PDGF-AA, A-PRF had a sustained release of growth factors released at later time points. Conclusion Results from the present study indicate that A-PRF is the most favourable form of platelet concentrate in regenerative periodontal therapy as it has a sustained release of growth factors over time.